Antisense Oligonucleotide: Basic Concepts and Therapeutic Application in Inflammatory Bowel Disease - Di Fusco, Davide; Dinallo, Vincenzo; Marafini, Irene; Figliuzzi, Michele M.; Romano, Barbara; Monteleone, Giovanni (Frontiers in Pharmacology, 2019)
Antisense oligonucleotide (ASO) technology is a specific, rapid, and potentially high-throughput method for inhibiting gene expression. ASO refers to a short synthetic strand of deoxy-ribonucleotide analogue that hybridizes with the complementary mRNA via Watson–Crick base pairing. The resulting RNA-DNA heteroduplex leads to a reduced translation of the target transcript thus inducing a blockade in the transfer of genetic information from DNA to protein. Crohn's disease (CD) and ulcerative colitis (UC), the major inflammatory bowel diseases (IBD) in humans, are clinically characterized by intermittent exacerbations and sometimes chronically active course. The causes of CD and UC are unknown and there is not a curative therapy for these patients. However, in the last decades, the advent of new techniques of molecular biology has largely advanced our understanding of the mechanisms that drive tissue damage in IBD. These progresses have facilitated the development of new therapeutic compounds, which selectively target molecules involved in IBD pathogenesis. This short review provides a comprehensive understanding of the basic concepts underlying the mechanism of action of ASOs and summarizes the available pre-clinical and clinical data for ASO-based therapy in IBD.